First Five Year Plan Bombay State Kolaba District - Government of Bombay (Government of Bombay, 1954)
The Five-Year Plan (1951-52 to 1955-56) for Kolaba District provides a structured and integrated framework for socio-economic development, targeting agriculture, education, health, rural development, and industrial growth. Agricultural initiatives focus on enhancing productivity through minor irrigation projects, embankments for coastal land protection, and improved cultivation techniques, alongside veterinary and animal husbandry programs, including breeding improvements for Dangi cattle. Education receives significant attention, with investments in primary and secondary schools, teacher training, and vocational programs emphasizing craft skills. Health measures, particularly malaria control using DDT spraying, maternal welfare programs, and rural medical services, aim to reduce disease prevalence and improve public health outcomes. The plan promotes cooperative development, strengthening farmer access to credit and fostering cottage industries, while infrastructure projects in road transport and power supply support economic connectivity and industrial growth. Rural development initiatives, including the Sarvodaya program, target sanitation, social services, and the economic upliftment of backward classes, complemented by legal and educational measures to combat untouchability and provide equitable opportunities. Community participation is emphasized through the Community Development Programme, integrating agriculture, education, and health improvements at the village level. Collectively, these strategies reflect a comprehensive vision for sustainable and inclusive growth, enhancing living standards, social equity, and long-term development potential in Kolaba District.
Kolaba District
Kolaba District
Keywords: Kolaba District; State Five Year Plan; Agricultural Development; Irrigation Projects; Education Initiatives; Health Services; Malaria Control; Rural Development; Cooperative Societies; Cottage Industries; Infrastructure Development; Backward Classes